Seasonal changes in the vertical structure of ozone in the Martian lower atmosphere and its relationship to water vapor - Olsen, KS; Fedorova, AA; Trokhimovskiy, A; Montmessin, F; Lefèvre, F; Korablev, O; Baggio, L; Forget, F; Millour, E; Bierjon, A; Alday, J; Wilson, CF; et al. (Wiley, 2022)
The mid-infrared channel of the Atmospheric Chemistry Suite (ACS MIR) onboard the ExoMars Trace Gas Orbiter is capable of observing the infrared absorption of ozone (O3) in the atmosphere of Mars. During solar occulations, the 003←000 band (3,000-3,060 cm−1) is observed with spectral sampling of ∼0.045 cm−1. Around the equinoxes in both hemispheres and over the southern winters, we regularly observe around 200–500 ppbv of O3 below 30 km. The warm southern summers, near perihelion, produce enough atmospheric moisture that O3 is not detectable at all, and observations are rare even at high northern latitudes. During the northern summers, water vapor is restricted to below 10 km, and an O3 layer (100–300 ppbv) is visible between 20 and 30 km. At this same time, the aphelion cloud belt forms, condensing water vapor and allowing O3 to build up between 30 and 40 km. A comparison to vertical profiles of water vapor and temperature in each season reveals that water vapor abundance is controlled by atmospheric temperature, and H2O and O3 are anti-correlated as expected. When the atmosphere cools, over time or over altitude, water vapor condenses (observed as a reduction in its mixing ratio) and the production of odd hydrogen species is reduced, which allows O3 to build up. Conversely, warmer temperatures lead to water vapor enhancements and ozone loss. The LMD Mars Global Climate Model is able to reproduce vertical structure and seasonal changes of temperature, H2O, and O3 that we observe. However, the observed O3 abundance is larger by factors between 2 and 6, indicating important differences in the rate of odd-hydrogen photochemistry.